Kiat-kiat Membangun Strategi Pembelajaran Emansipatoris pada Pendidikan Dasar Islam - Muhammad Arif Syihabuddin (Indonesian Journal of Islamic Education Studies (IJIES), 2019)
This article discusses about emancipatory education, the main focus is the strategy of building emancipatory education. Education has a close relationship with social change, both in the form of dynamics of individual development and social processes on a broader scale. This study of emancipatory education is important, because in this globalization era Education is one of the decisive aspects, especially in opening the way to liberation from poverty, ignorance and adversity. Emancipatory meaning is human liberation from fetters in the context of Education, this emancipatory idea is expected to be able to give new colors and changes to the process and implementation of Education which has been regarded as giving less freedom. The liberation paradigm is the main basis of emancipatory education. This liberation makes an education play a role in freeing students from ignorance, retardation, obedience and immorality. There are several efforts that must be made in building an emancipatory learning strategy on Islamic Education. First, shifting the focus of attention from religion to religiosity. Second, enter plurality. Third, emphasizing the formation of attitudes. Then there are three keys in the emancipatory Education model, namely: humanization, critical and democratic awareness.